KEMAMPUAN BERPIKIR KREATIF MATEMATIS DITINJAU DARI SELF CONCEPT SISWA PADA MATERI BANGUN DATAR DI SMP - Muniroh, Badriyatul; Hartoyo, Agung; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to know and describe mathematic creative thinking comprehension reviewed from student’s self-concept on two-dimensional figure matter at class VIII SMP Negeri 1 Sungai Raya. Research method used is descriptive in the form survey research. Sample of this research is class VIII with 31 students. The data obtained is self-concept questionnaire result and student’s answer sheet to questions related to two-dimensional matter. The research result shows that student’s mathematic creative thinking comprehension with high self-concept categorized very creative (25%) and less creative (75%); student’s mathematic creative thinking comprehension with average self-concept categorized creative (62,5%), less creative (33,33%) and not creative (4,17%); and student’s mathematic creative thinking comprehension with low self-concept categorized less creative (100%).Keyword: mathematic creative thinking comprehension, self-concept